(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
When growing environmentally friendly and high-quality barley grain for technological processes, an important role is played by the optimization of norms and proportions of mineral fertilizers, as well as the optimization of seeding rates. In our scientific study, when preparing barley grain for technological processes, sowing rates and nutritional factors that affect a number of technological indicators, such as the weight of 1000 grains, natural weight, were widely studied